Evaluation of Acute and Sub-Chronic Toxicity of Lactobacillus rhamnosus GG in Sprague-Dawley Rats - Vedam Venkata Kanthi Vaishnavi; Urmila Banik; Gokul Shankar Sabesan; Arun K. Adhikary; Subramani Parasuraman (Advanced Biomedical Research)
Background: Probiotic-based bacteriotherapy has emerged as a potentially effective strategy for preventing infectious diseases. Lactobacillus strains consumed as probiotics and the safety of these spp. has been questioned due to reported unexpected responses. Hence, the present study has been conducted to evaluate the acute and sub-chronic toxicity of Lactobacillus rhamnosus GG in Sprague-Dawley (SD) rats. Materials and Methods: The acute and sub-chronic toxicity effect of L. rhamnosus is studied in rats as per the Organization for Economic Cooperation and Development (OECD), test guideline 423 and 407, respectively. Results: In acute toxicity, L. rhamnosus at 1 × 107, 1 × 108, 1 × 109, and 1 × 1010 CFU/mL don’t show any toxic signs. In sub-chronic toxicity, L. rhamnosus at 1 × 106,1 × 107 and 1 × 108 CFU/mL dosages showed dose-depended changes in biochemical and haematological parameters. In this study, one male and one female rat administered with 1 x 108 CFU/mL of L. rhamnosus showed mortality on days 16 and 26, respectively. The animals administered with L. rhamnosus showed no histological changes in the organs such as heart, liver and kidney. Conclusion: L. rhamnosus exhibited mild-to-moderate toxic effects at the dose levels of 1 × 106 CFU/mL, 1 × 107 and 1 × 108 CFU/mL in rats.